PENGARUH RISIKO AUDIT, TEKANAN WAKTU, PENGALAMAN AUDITOR DAN EQUITY SENSITIVITY TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT (Studi Kasus Pada Kap Jakarta Selatan) - Tamariska Christianti; Eko Suyono; Yusriyati Nur Farida (Jurnal Inovasi Penelitian, 2021)
This study aims to determine whether audit risk, time pressure, auditor experience and equity sensitivity affect premature termination of audit procedures at the Public Accounting Office in South Jakarta. The population in this study are auditors who work at the Public Accounting Firm in South Jakarta and have positions as partners, managers, senior auditors, supervisors and junior auditors and have at least 1 year of work experience, the sampling method is pirposive sampling and samples are taken totaled 89 auditors. The data obtained were analyzed using multiple linear regression analysis techniques.The results in this study indicate: (1) Audit risk has a positive and significant effect on premature termination of audit procedures. (2) Time Pressure has a positive and significant effect on premature termination of audit procedures. (3) Auditor's experience has a negative and significant effect on premature termination of audit procedures. (4) Equity Sensitivity has a negative and insignificant effect on premature termination of audit procedures. The implication of this research is premature termination of audit procedures by taking into account the influencing factors such as Audit Risk, Time Pressure, Auditor Experience and Equity Sensitivity.